1869 Mich. Pub. Acts 2d Reg. Sess. 157-58, No. 247, § 15. - (:unkn) unknown (General Publisher, 1869)
[T]he common council shall have full power and authority to make by laws and ordinances . . . relative to keeping and sale of gunpowder, nitroglycerine, and all other dangerous and explosive articles, or burning fluids.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER